Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.14245/ns.2040236.118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Body Mass Index on Perioperative Outcomes in Patients Undergoing Anterior Cervical Discectomy and Fusion Surgery

Abstract: Objective Obesity has become a public health crisis and continues to be on the rise. An elevated body mass index has been linked to higher rates of spinal degenerative disease requiring surgical intervention. Limited studies exist that evaluate the effects of obesity on perioperative complications in patients undergoing anterior cervical discectomy and fusion (ACDF). Our study aims to determine the incidence of obesity in the ACDF population and the effects it may have on postoperative inpatient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…The authors have suggested the association between obesity and early-dysphagia may be linked to the increased thickness of the prevertebral tissue in obese patients, leading to difficulty in manipulation and excessive esophageal retraction. 26,30,31 Finally, while no past study has elucidated the implication of frailty in the development of dysphagia, the present publication demonstrated a significant association. Frailty which is defined as hypoalbuminemia, muscle weakness or fatigue may make patients especially susceptible to more intraoperative tissue manipulation and thus at increased risk of postoperative dysphagia.…”
Section: Patient Related Risk Factorsmentioning
confidence: 41%
See 1 more Smart Citation
“…The authors have suggested the association between obesity and early-dysphagia may be linked to the increased thickness of the prevertebral tissue in obese patients, leading to difficulty in manipulation and excessive esophageal retraction. 26,30,31 Finally, while no past study has elucidated the implication of frailty in the development of dysphagia, the present publication demonstrated a significant association. Frailty which is defined as hypoalbuminemia, muscle weakness or fatigue may make patients especially susceptible to more intraoperative tissue manipulation and thus at increased risk of postoperative dysphagia.…”
Section: Patient Related Risk Factorsmentioning
confidence: 41%
“…Similarly, Wang et al [ 26 ] and Liu et al [ 30 ] found increased rates in the immediate postoperative period only. The authors have suggested the association between obesity and early-dysphagia may be linked to the increased thickness of the prevertebral tissue in obese patients, leading to difficulty in manipulation and excessive esophageal retraction [ 26 , 30 , 31 ]. Finally, while no past study has elucidated the implication of frailty in the development of dysphagia, the present publication demonstrated a significant association.…”
Section: Discussionmentioning
confidence: 99%
“…(25) Obese patients had a greater potential for complications such as intra-operative durotomy, dysphagia, neurological, cardiopulmonary, and hematologic complications following ACDF procedures. (26) Basques et al reported that obesity did not impact clinical outcomes but affected cervical sagittal alignment and adjacent segment degeneration in a short term follow-up after ACDF. (27) In the current study, although the two cases with postoperative dysphagia were classified as obese, after multivariate analysis, the author found the relationship without statistical significance.…”
Section: /11 Journal Of Southeast Asian Medical Research E0104mentioning
confidence: 97%
“…Yet, as our population continues to age and thus continues to develop and live with chronic illnesses, perioperative harm reduction becomes ever more imperative. Diabetes mellitus (DM), obesity, systemic malignancy, and cardiovascular disease are all conditions associated with an increased risk of perioperative adverse events in spine surgery [1]. However, hypothyroidism, which carries a prevalence of approximately 1%-4% in the US and has been independently associated with the development of hypertension, cardiovascular disease, osteoporosis, peripheral neuropathy, muscular weakness, and increased complication rates in non-spinal surgeries, has had only a limited number of studies suggesting that it confers increased perioperative risk in patients undergoing major spine surgery [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%